Characterising and deriving engineering properties of a saprolitic soil from granite, in Porto - A. Viana da Fonseca (2003)
Residual soils are characterised by the presence of a bonded structure and fabric that has significant influence on engineering behaviour. This characteristic requires specific concepts for geotechnical classification. Micro and macrofabric analysis can easily clarify the potential for more or less pronounced metastability. Deformational behaviour, pre-yield and post yield, is related to fairly well defined state regions. A good definition of constitutive laws of these soils demands careful experimental work and parametric analysis both from in situ and laboratory testing. A typical profile of a saprolitic soil from granite in Porto was studied. Several in situ testing techniques (CH, SPT, CPT, PMT, SBPT, DMT, PLT and a full-scale footing testing) were used in order to have a very sound knowledge of the mechanical characteristics of this soil. High quality undisturbed block samples were recovered and an extensive laboratory testing programme was carried out, including isotropic and oedometric consolidation tests, as well as CID and CK0D triaxial tests using local strain measuring devices. This paper presents and discusses the results obtained, giving emphasis to the interpretation of constitutive behaviour differences in stressstrain levels lower and higher than the yield stresses related to saprolitic soils with weak relic structures.